Evaluation of Gastrointestinal Leakage in Multiple Enteric Inflammation Models in Chickens - Kuttappan, Vivek A.; Vicuña, Eduardo A.; Latorre, Juan D.; Wolfenden, Amanda D.; Téllez, Guillermo I.; Hargis, Billy M.; Bielke, Lisa R. (Frontiers in Veterinary Science, 2015)
Enteric inflammation models can help researchers study methods to improve health and performance plus evaluate various growth promoters and dietary formulations targeted to improve performance in poultry. Oral administration of fluorescein isothiocyanate dextran (FITC-d; 3-5 kDa) and its pericellular mucosal epithelial leakage is an established marker to evaluate enteric inflammation in multiple species. The present study evaluated different methods to induce gut inflammation in poultry based on FITC-d leakage. Four independent experiments were completed with different inflammation treatment groups; serum FITC-d and/or retention of FITC-d in GI tract was/were determined. In experiment 1 (n=10 birds/treatment; broilers; processed at 14d), groups included control (CON), Dextran sodium sulfate (DSS; drinking water at 0.75%) and feed restriction (FRS; 24h before processing). Experiment 2 (n=14birds/treatment; leghorns; processed at 7d) included CON, DSS, FRS, and rye based diet (RBD). In experiments 3 and 4 (n=15 birds/treatment; broilers; processed at 7d), groups were CON, DSS, high fat diet (HFD), FRS, and RBD. In all experiments, FRS and RBD treatments showed significantly higher serum FITC-d levels compared to the respective CON. This indicates that FRS and RBD results in disruption of the intact barrier of the GIT, resulting in increased gut permeability. DSS and HFD groups showed elevation of serum FITC-d levels although the magnitude of difference from respective CON were inconsistent between experiments. FRS was the only treatment which consistently showed elevated retention of FITC-d in GIT in all experiments. The results from present studies showed that FRS and RBD, based on serum FITC-d levels, can be robust models to induce gut leakage in birds in different age and species/strains.